Superação da dormência em sementes de Enterolobium schomburgkii (Benth.) na região de Santarém, Pa - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The seed of Enterolobium schomburgkii (Benth.), Known as fava orelha de macaco, has integument dormancy in which dormancy overcoming methodologies are necessary for germination. This work aims to try different pre-germination treatments for the breakdown of dormancy. The seeds were stored at room temperature for 15 days and then received the following treatments: T1- Testimony; T2- chemical scarification of H2SO4 for 2 min; T3- chemical scarification of H2SO4 for 5 min; T4- chemical scarification of H2SO4 for 15 min; T5- chemical scarification of H2SO4 for 30 min; T6- mechanical scarification with sandpaper; T7- mechanical scarification with sandpaper, followed by imbibition in water; T8- mechanical scarification in mechanical blender; T9- mechanical scarification in mechanical blender, followed by imbibition in water; T10- Thermal by immersion in water at 100 ° C cooling to room temperature (30 ° C), after application of the treatments were placed in Gerbox box with two sheets of gemitest paper, stored in Biochemical Oxigen Demand, in a randomized block design, under 30 ° C and external photoperiod light. In order to compare the treatments, the percentage of emergence, germination speed index, mean emergence time and germination speed coefficient were evaluated. The chemical scarification with 95% sulfuric acid for 15 and 30 minutes was the most efficient in comparison to the other treatments. However, the following treatments may be recommended: mechanical scarification with sandpaper + water immersion for 30 minutes, and mechanical scarification with mechanical scarifier + water immersion for 30 minutes, to overcome dormancy in E. schomburgkii seeds.
Keywords: Tratamento de semente; Sementes florestais; Impermeabilidade do tegumento; Vigor; CNPQ:: CIÊNCIAS AGRÁRIAS